Synthesis and Characterisation of PVP-AAm Hydrogels via Hybrid Process: Morphological, Physical, and Antibacterial Activity - Fatma Nur Parın (Journal of Advanced Research in Natural and Applied Sciences)
Hydrogels are three dimentional networks that constitute of either chemical or physical crosslinks. In this study, preparation of polyvinyl pyrolidone/polyacrylamide (PVA/PAAm) hydrogels exhibiting antibacterial property was demonstrated. Bio-derived α-bisabolol, d-limonene, and geraniol were utilized as antibacterial agents, whereas stabilization of PVA/PAAm hydrogels was achieved by using beta-cyclodextrin (β-CD). PVA/AAm polyblend solutions were polymerizided via UV-irradiation. Then freeze-thawing and anneal-swelling were respectively carried out. Once the morphological, physical properties of the resulting hydrogels was characterized antibacterial efficiency tests were also performed. In the end, it was demonstrated that PVP/PAAm/α-bisabolol and PVP/PAAm/geraniol hydrogels have good antibacterial properties against Escherichia coli with 9 mm zone inhibition.